2020
DOI: 10.1186/s40249-020-00724-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 on medical care workers in China

Abstract: Background: Medical care workers experienced unprecedented levels of workload and pressure since the outbreak of coronavirus disease 2019 (COVID-19). Little is known about its exact impact on medical care workers and related factors in China. This study aims to identify the psychological impact of COVID-19 on medical care workers in China. Methods: From February 23 to March 5, 2020, a cross-sectional survey was conducted among 863 medical care workers from seven provinces in China using standard questionnaires… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
162
5
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(230 citation statements)
references
References 36 publications
(55 reference statements)
20
162
5
11
Order By: Relevance
“…According to the literature, lack of social support is a known predictor of occupational stress in HCWs [ 37 , 38 ], and it is defined as “the feeling that one is cared for and has assistance available from other people” and “that one is part of a supportive social network” [ 38 ]. As revealed by Si et al [ 21 ], a supportive work environment is a buffering factor of negative psychological health among HCWs and protects them from PTSS during the COVID-19 pandemic; in fact, in their study, the authors found that social support had the greatest impact on the mental health of HCWs: low (OR: 5.49, 95% CI: 4.04, 7.45) and moderate (OR: 2.73, 95% CI: 2.42, 3.07) levels of social support were associated with a higher risk of PTSD compared to high levels of social support [ 19 ].…”
Section: Discussionmentioning
confidence: 88%
“…According to the literature, lack of social support is a known predictor of occupational stress in HCWs [ 37 , 38 ], and it is defined as “the feeling that one is cared for and has assistance available from other people” and “that one is part of a supportive social network” [ 38 ]. As revealed by Si et al [ 21 ], a supportive work environment is a buffering factor of negative psychological health among HCWs and protects them from PTSS during the COVID-19 pandemic; in fact, in their study, the authors found that social support had the greatest impact on the mental health of HCWs: low (OR: 5.49, 95% CI: 4.04, 7.45) and moderate (OR: 2.73, 95% CI: 2.42, 3.07) levels of social support were associated with a higher risk of PTSD compared to high levels of social support [ 19 ].…”
Section: Discussionmentioning
confidence: 88%
“…Hypervigilance, which is our highest increased symptoms during COVID-19, was not measured in previous studies. Symptoms as distress [ 12 , 13 , 16 ] and decreased appetite or indigestion are also frequently reported [ 12 ]. Our results are also in line with negative professional symptoms as stopping with the present job [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that physicians and nurses had higher BAI and PSS scores than other staff, and scores of nurses were significantly higher than the physicians. This may be due to the fact that nurses are always in close contact with a variety of patients with various illnesses, with different socio-economic status and perform procedures including blood sampling and throat swab sampling, therefore, they are in the group with the highest risk of having COVID-19 [24]. The healthcare workers who are most in contact with the patient and most at risk should be considered more during the infectious disease outbreaks and should be supported psychologically [25].…”
Section: Discussionmentioning
confidence: 99%